ENSO Amplitude Asymmetry in Met Office Hadley Centre Climate Models - Ineson, Sarah; Dunstone, Nick J.; Ren, Hong-Li; Renshaw, Richard; Roberts, Malcolm J.; Scaife, Adam A.; Yamazaki, Kuniko (Frontiers in Climate, 2021)
Long climate simulations with the Met Office Hadley Centre General Circulation Model show weak El Niño Southern Oscillation (ENSO) amplitude asymmetry between El Niño and La Niña phases compared with observations. We explore this lack of asymmetry through the framework of a perturbed parameter experiment (PPE). We test two key hypotheses for the lack of asymmetry. First, we test for errors in westerly wind burst activity. We show that the observed modulation in modelled wind burst activity associated with ENSO tends to be underestimated by the PPE. Secondly, we examine the warming due to subsurface nonlinear advection. While the model exhibits nonlinear dynamic warming during both La Niña and El Niño, and thus a contribution to ENSO asymmetry, we show that it is consistently underestimated in comparison with ocean reanalyses. The nonlinear zonal advection term contributes most to the deficiency and the simulation of the anomalous zonal currents may be playing a key role in its underestimation. Compared with the ocean reanalyses, the anomalous zonal currents associated with ENSO are too weak in the vicinity of the equatorial undercurrent and that surface wind driven zonal currents extend too deep.